Изменение скорости звука при водородном охрупчивании стали 40Х13 - Баранникова С. А. Светлана Александровна; Лунёв А. Г. Алексей Геннадьевич; Бочкарёва А. В. Анна Валентиновна; Зуев Л. Б. Лев Борисович (2015, 2015)
Заглавие с экрана